PENGARUH KEPERCAYAAN DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN YANG DIMEDIASI OLEH VARIABEL KEPUASAN PADA PT. INDAH LOGISTIK CARGO DI KOTA LANGSA - Cika Febita Br.sijabat; Halimatussakdiah Halimatussakdiah (Departemen Manajemen, 2022)
This study aims to determine the effect of trust and service quality on customer loyalty mediated by satisfaction variables at PT. Beautiful Logistics Cargo in Langsa City. This research is a quantitative study, using questionnaires as a data collection instrument. The population in this study was Indah Logistik Cargo customers totaling 200 people. The sampling technique used is purposive sampling. The data analysis method used is Structural Equation Modelling (SEM) used as an analysis method to determine the influence between the variables involved. Based on the results of the SEM analysis, trust has a significant effect on loyalty, service quality has a significant effect on customer loyalty. Trust has a significant effect on customer satisfaction, service quality has a significant effect on customer satisfaction, Satisfaction has a significant effect on loyalty, Satisfaction mediates trust in customer loyalty and Satisfaction mediates the quality of service to customer loyalty.